Cardiovascular magnetic resonance patterns of biopsy proven cardiac involvement in systemic sclerosis. Issue 1 (January 2017) - Krumm, Patrick; Mueller, Karin; Klingel, Karin; Kramer, Ulrich; Horger, Marius; Zitzelsberger, Tanja; Kandolf, Reinhard; Gawaz, Meinrad; Nikolaou, Konstantin; Klumpp, Bernhard; Henes, Joerg
Abstract Background To determine morphological and functional cardiovascular magnetic resonance (CMR) patterns in histopathologically confirmed myocardial involvement in patients with systemic sclerosis (SSc). Methods Twenty patients (6 females; mean age 41 ± 11 years) with histopathologically proven cardiac involvement in SSc in the years 2008–2016 were retrospectively evaluated. Morphological, functional and late gadolinium enhancement (LGE) images were acquired in standard angulations at 1.5 T CMR. Pathologies were categorized: 1) Pericardial effusion; 2) pathologic left (LV) or right ventricular (RV) contractility (hypokinesia, dyssynchrony, and diastolic restriction); 3) reduced left (LV-EF) and right ventricular ejection fraction (RV-EF); 4) fibrosis and/or inflammation (positive LGE); 5) RV dilatation. 95 % confidence intervals (CI) were calculated for appearance of pathologic EF and RV dilatation. Results Seven patients (35 %) had positive CMR findings in three categories, 9 patients (45 %) in four categories and 4 patients (20 %) in five categories. The distribution of pathologic findings was: minimal pericardial effusion in 7 patients (35 %), moderate pericardial effusion >5 mm in nine patients (45 %); abnormal LV or RV contractility in 19 patients (95 %), reduced LV or RV function in 14 patients (70 %; 95 % CI: 51–88 %), pathologic LGE in all patients, RV dilatation in 6 patients (30 %; 95 % CI: 15–54 %). Conclusions CMR diagnosis of myocardial involvement in SSc requires increased attention to subtle findings. Pathologic findings in at least three of five categories indicate myocardial involvement in SSc.